The Th17 Pathway in Vascular Inflammation: Culprit or Consort? - Robert, Marie; Miossec, Pierre; Hot, Arnaud (Frontiers in Immunology, 2022)
The involvement of IL-17A in autoimmune and inflammatory diseases has prompted the development of therapeutic strategies to block the Th17 pathway. Promising results came from their use in psoriasis and in ankylosing spondylitis. IL-17A acts on various cell types and has both local and systemic effects. Considering the premature mortality observed during chronic inflammatory diseases, IL-17A action on vascular cells was studied. Both in vitro and in vivo results suggest that this cytokine favors inflammation, coagulation and thrombosis and promotes the occurrence of cardiovascular events. These observations led to study the role of IL-17A in diseases characterized by vascular inflammation, namely allograft rejection and vasculitis. Increased circulating levels of IL-17A and histological staining reveal that the Th17 pathway is involved in the pathogenesis of these diseases. Vasculitis treatment faces challenges while the use of steroids has many side effects. Regarding results obtained in giant cell arteritis with IL-6 inhibitors, a cytokine involved in Th17 differentiation, the use of anti-IL-17 is a promising strategy. However, lessons from rheumatoid arthritis and multiple sclerosis must be learnt before targeting IL-17 in vasculitis, which may be culprit, consort or both of them.